PENERAPAN SISTEM AKUNTANSI CLOUD UNTUK PENGELOLAAN KEUANGAN KELOMPOK USAHA UMKM NAIK KELAS BOGOR - Hartanti, Hartanti; Ratiyah, Ratiyah; Riftiasari, Dinar (Jurnal AbdiMas Nusa Mandiri, 2025)
This community service program aims to enhance the managerial capacity, financial literacy, and digital competence of Micro, Small, and Medium Enterprises (MSMEs) under the Naik Kelas Bogor initiative through the implementation of a cloud-based accounting system, SILAKU SMART. MSMEs in Bogor contribute significantly to the local economy; however, they still face challenges in accurate bookkeeping, financial reporting, human resource management, and digital marketing. The program was implemented from July to December 2025, with intensive training conducted in September–October 2025, involving MSME participants from various sectors, particularly home-based culinary businesses. The program adopted a systematic approach consisting of socialization, participatory training, cloud application implementation, mentoring, and evaluation. The results showed a significant improvement in participants’ understanding of the cloud-based accounting system, with 70% of participants being highly proficient after the second training session. Moreover, 90% of participants expressed strong confidence in applying cloud accounting, managerial practices, and digital marketing in their businesses. The implementation of SILAKU SMART also enabled real-time transaction recording, automatic financial reporting, and integration with digital marketing features, which enhanced operational efficiency and expanded market reach. This program aligns with the Sustainable Development Goals (SDGs), particularly in promoting decent work and economic growth (Goal 8), fostering innovation and infrastructure development (Goal 9), and strengthening partnerships for sustainable development (Goal 17). These findings demonstrate that the combination of digital technology and participatory training can effectively empower MSMEs, enhance business professionalism, and strengthen competitiveness in the digital economy.